Just enough Chinese - Ellis, D.L; McKillop, Beth; Guo, Jin; Jin, Hong (Passport Books, a division of NTC/Contemporary Publishing Group, Inc., 1991)
Each book in this series provides just the right phrases to get by and be easily understood in everyday situations in foreign countries. Travelers will appreciate these essential phrases for crossing borders; changing money; asking directions; meeting people; and finding accommodations, the post office, telephones, shopping areas, and transportation.